Humoral immune responses in different stages of wound healing in Black Bengal goats - Samaddar, Kanika; Rahman, Mohammad Habibur; Leon, Md Leonur Islam; Rana, Md Sohel; Hasan, Md Mehedi; Haque, Ziaul; Rahman, Md Mizanur (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The current study was carried out to assess the humoral immune responses according to age at different stages of wound healing in Black Bengal goats (BBG). Materials and Methods: Apparently, healthy BBGs (n = 20) were collected and divided into five groups based on their age: Group A (control, 3 years), Group B (3 to 5 years), Group C (2 to <3 years), Group D (1 to <2 years), and Group E (<1 year). Except for control, all BBGs were allowed to have artificial surgical wounds, and follow-up data were collected from day 0 to 21. The humoral immune responses [immunoglobulins (Igs) and interleukin-6 (IL-6)] were determined by ELISA using commercial goat ELISA kits. Statistical Product and Service Solutions (Version 20) was used to analyze the data. Results: The normal range of immune cells in control BBGs was immunoglobulin G (IgG) (20.21 ± 0.13 mg/ml), immunoglobulin M (IgM) (2.87 ± 0.0.05 mg/ml), immunoglobulin A (IgA) (0.33 ± 0.01 mg/ml), and IL-6 (1.6 ± 0.05 pg/ml). In this experiment, higher concentrations of IgG (21.11 ± 0.20 mg/ml), IgM (2.92 ± 0.04 mg/ml), IgA (0.35 ± 0.02 mg/ml), and IL-6 (1.62 ± 0.05 pg/ml) were found in Group B BBGs, whereas the lower levels of IgG, IgM, IgA, and IL-6 were found at 17.16 ± 0.18 mg/ml, 2.12 ± 0.01 mg/ml, 0.29 ± 0.03 mg/ml, and 1.55 ± 0.05 pg/ml, respectively, in the Group E BBGs. Rapid wound healing was observed in the older groups compared to the younger groups of BBGs. The concentrations of Igs (IgG, IgM, and IgA) and IL-6 were gradually increased in all groups from day 3 (early inflammatory stage) and day 7 (late inflammatory stage), and then they decreased gradually from day 14 (proliferative stage) to reach the final stage of day 21 (remodeling stage), where the concentrations were found to be at a level comparable to their per-incisional period. No gender-related differences were detected. Conclusion: Adult BBGs (3 to 5 years old) showed faster wound repair and stronger immune responses. This finding may assist veterinarians and researchers in considering age-related immune responses for the recovery and rapid cure of surgical wounds. J. Adv. Vet. Anim. Res., 10(3): 361–369 September 2023 http://doi.org/10.5455/javar.2023.j688